STEM Education: Present Status and Future Direction - Malcolm Homavazir; Zuleika Homavazi (AG Volumes, 2024)
The most effective way to develop and utilise a nation’s enormous resources and capabilities for benefit of individuals, society, nation, and the world is to provide universal, high-quality education. The Union Cabinet of India granted approval to the National Education Policy 2020 (NEP 2020), which establishes the objectives for India’s forthcoming education system, on July 29, 2020. By substituting the National Policy on Education from 1986. NEP 2020’s alignment with promoting STEM (science, technology, engineering & mathematics) education, systematic implementation are the subjects of this conceptual paper.